IgG in the control of FcεRI activation: a battle on multiple fronts - Storni, Federico; Vogel, Monique; Bachmann, Martin F.; Engeroff, Paul (Frontiers in Immunology, 2024)
The rising global incidence of IgE-mediated allergic reactions poses a significant challenge to the quality of life of affected individuals and to healthcare systems, with current treatments being limited in effectiveness, safety, and disease-modifying capabilities. IgE acts by sensitizing the high-affinity IgE receptor FcεRI expressed by mast cells and basophils, tuning these cells for inflammatory degranulation in response to future allergen encounters. In recent years, IgG has emerged as an essential negative regulator of IgE-dependent allergic inflammation. Mechanistically, studies have proposed different pathways by which IgG can interfere with the activation of IgE-mediated inflammation. Here, we briefly summarize the major proposed mechanisms of action by which IgG controls the IgE-FcεRI inflammatory axis and how those mechanisms are currently applied as therapeutic interventions for IgE-mediated inflammation.